How does coumarin work in insulin resistance for diabetes mellitus type 2? (A literature review) - Arwani Arwani; Afifah Salsabila (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Coumarin is a natural compound found in various plants, including Cinnamomum cassia and Cinnamomum zeylanicum, and has been widely studied for its potential role in metabolic regulation, particularly in diabetes mellitus type 2. While coumarin has shown potential benefits in improving glycemic control, concerns regarding its hepatotoxic and carcinogenic effects remain. Purpose: To review the literature on how coumarin works in insulin resistance in people with type 2 diabetes. Method: A literature review was conducted using the ClinicalKey, Science Direct, and Google Scholar databases. Boolean operators (AND, OR, NOT) were used to refine the search. Inclusion criteria included research articles published between 2015 and 2024 in accredited national or internationally reputable journals, with a JBI critical appraisal tools score above 65%. The PRISMA diagram was used for article selection, resulting in five eligible articles for analysis. Results: The findings indicate that coumarin, predominantly found in cinnamon, has glucose-lowering effects in diabetes mellitus type 2 patients by reducing blood glucose levels, controlling glucose spikes, and lowering HbA1c. Additionally, coumarin derivatives in Opuntia ficus-indica and Smallanthus sonchifolius (yacon) may contribute to metabolic homeostasis through antioxidant activity. However, coumarin also poses hepatotoxic and carcinogenic risks at high doses. Conclusion: While coumarin-containing compounds show promise in improving glycemic control. Further research is needed to determine safe and effective therapeutic doses for clinical application.